CXCR4 expression is associated with proneural‐to‐mesenchymal transition in glioblastoma. Issue 4 (31st October 2022) - Khan, A. Basit; Lee, Sungho; Harmanci, Akdes Serin; Patel, Rajan; Latha, Khatri; Yang, Yuhui; Marisetty, Anantha; Lee, Hyun‐Kyoung; Heimberger, Amy B.; Fuller, Gregory N.; Deneen, Benjamin; Rao, Ganesh
Abstract: Glioblastoma (GBM) is the most common primary intracranial malignant tumor and consists of three molecular subtypes: proneural (PN), mesenchymal (MES) and classical (CL). Transition between PN to MES subtypes (PMT) is the glioma analog of the epithelial‐mesenchymal transition (EMT) in carcinomas and is associated with resistance to therapy. CXCR4 signaling increases the expression of MES genes in glioma cell lines and promotes EMT in other cancers. RNA sequencing (RNAseq) data of PN GBMs in The Cancer Genome Atlas (TCGA) and secondary high‐grade gliomas (HGGs) from an internal cohort were examined for correlation between CXCR4 expression and survival as well as expression of MES markers. Publicly available single‐cell RNA sequencing (scRNAseq) data was analyzed for cell type specific CXCR4 expression. These results were validated in a genetic mouse model of PN GBM. Higher CXCR4 expression was associated with significantly reduced survival and increased expression of MES markers in TCGA and internal cohorts. CXCR4 was expressed in immune and tumor cells based on scRNAseq analysis. Higher CXCR4 expression within tumor cells on scRNAseq was associated with increased MES phenotype, suggesting a cell‐autonomous effect. In a genetically engineered mouse model, tumors induced with CXCR4 exhibited a mesenchymal phenotype and shortened survival. These results suggest that CXCR4 signaling promotes PMT and shortens survival in GBM and highlights its inhibition as a potential therapeutic strategy. Abstract : What's new? Glioblastoma (GBM) is characterized by three distinct molecular subtypes, proneural, mesenchymal and classical. The transition from proneural to mesenchymal subtypes marks increased resistance to therapy In our study, the expression of CXCR4, a chemokine receptor associated with invasive GBM phenotypes, was investigated for its relationship with survival and expression of MES markers in GBM. Analyses show that elevated CXCR4 expression is linked to shorter survival and increased expression of MES markers in proneural GBM, in both bulk and single‐cell RNA sequencing. In a mouse model of proneural GBM, CXCR4 expression was enough to induce the transition to mesenchymal disease.